Insertional torque and pullout strength of reinserted screws for sacroiliac joint fusion: Effects of implant dimensions, bone density, and tapping - Cale J. Hendricks, BS; David W. Polly, Jr, MD; Ashley M. Abbott, BS; Yaqoub Y. Yusuf, MS; Rafael A. Garcia, BS; Matthew R. MacEwen, PhD; Arin M. Ellingson, PhD (North American Spine Society Journal, 2025)
Background: Sacroiliac joint (SIJ) fusion is a common procedure for SIJ pain and dysfunction. Traditional threaded screws offer limited bony integration, prompting the development of additively manufactured, porous implants aimed at enhancing osseointegration. However, data on their insertional mechanics and pullout strength, especially in revision scenarios, remain sparse. This study aimed to investigate the influence of bone density, tapping, and implant size on re-insertional torque and pullout strength. Methods: Mechanical testing was conducted in accordance with ASTM F543, using 10 and 20 PCF polyurethane foam blocks to simulate low and normal-density bone, respectively. A 10 × 35 mm screw fusion device served as the control. For subsequent tests, the 10 × 35 mm screw was removed, and various diameters (10, 11.5, 13.5 mm) and lengths (35, 40, 45 mm) were reinserted under 2 conditions: direct and with tapping. The maximum and final insertional torque, as well as the maximum pullout force, were measured. ANOVA techniques with pairwise comparison and Pearson correlation tests were performed (α = 0.05). Results: Significant effects and interactions were observed for implant size, bone density, and tapping. Larger implant diameter and length were associated with significantly greater insertional torque and pullout strength compared to controls, though excessively large diameters yielded diminishing returns in normal-density bone. Independent of size and tapping, normal-density bone consistently demonstrated greater insertional torque (929.1 ± 6.5 vs. 235.0 ± 6.5N·cm) and pullout strength (1,331.2 ± 14.8 vs. 457.3 ± 14.6 N) than low-density bone (p < .001). Independent of size, tapping improved insertional torque (+33.9%; p < .001) and pullout strength (+108.4%; p < .001) in normal-density bone but reduced pullout strength in low-density bone (−22.4%; p < .001). Final insertional torque strongly correlated with pullout strength (r = 0.946, p < .001). Conclusions: Our findings provide evidence-based insight for optimizing implant selection and surgical technique in revision SIJ fusion procedures using screw fusion devices. Particularly, it is emphasized that both implant dimensions and patient-specific bone quality must be considered to achieve stable and successful outcomes.